2014
DOI: 10.1021/jo5018876
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Progress Kinetic Analysis of a Copper-Catalyzed Aerobic Oxidative Coupling Reaction withN-Phenyl Tetrahydroisoquinoline

Abstract: The results from a kinetic investigation of a Cu-catalyzed oxidative coupling reaction between N-phenyl tetrahydroisoquinoline and a silyl enol ether using elemental oxygen as oxidant are presented. By using reaction progress kinetic analysis as an evaluation method for the obtained data, we discovered information regarding the reaction order of the substrates and catalysts. Based on this information and some additional experiments, a refined model for the initial oxidative activation of the amine substrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 55 publications
2
21
0
1
Order By: Relevance
“…Initial experiments were designed to examine the stability of the catalyst under synthetically relevant conditions. [9,10] The conversion of 4 into 5 in the presence of 10 mol %catalyst was monitored by following [5]a nd subsequently plotting [4]a s af unction of time ( Figure 3). Ah igher catalyst loading was employed to ensure reproducible detection of the titanocene species and to obtain fast turnover.…”
mentioning
confidence: 99%
“…Initial experiments were designed to examine the stability of the catalyst under synthetically relevant conditions. [9,10] The conversion of 4 into 5 in the presence of 10 mol %catalyst was monitored by following [5]a nd subsequently plotting [4]a s af unction of time ( Figure 3). Ah igher catalyst loading was employed to ensure reproducible detection of the titanocene species and to obtain fast turnover.…”
mentioning
confidence: 99%
“…In its absence, neither 5 nor 6 afforded any coupling product under the conditions used. The previously demonstrated simple copper salts, such as CuCl and CuCl 2 , could also catalyse the aerobic coupling, and showed similar activity in the absence or presence of TBAC (Table , entries 13–16). They are, however, much less effective than the combination of 1 and TABC, and afforded 4 a in <60 % yield in a prolonged time of 12 h under the conditions given in Table .…”
Section: Resultsmentioning
confidence: 77%
“…They also demonstrated that the coupling with nitroalkanes can be conducted with O 2 or electrochemically . Klussmann and co‐workers recently revealed that CuCl 2 also catalyses the CDC reaction of N ‐aryl tetrahydroisoquinolines with a number of nucleophiles and, more interestingly, oxygen can be used as the terminal oxidant for this wide range of nucleophiles . We note that with these simple copper salts, the catalyst loading is usually high, typically 5–10 mol %.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations